Advanced emergency braking system reduces the risk of motor vehicle collisions caused by falling asleep while driving in patients with untreated obstructive sleep apnea. (26th August 2022) - Arita, Aki; Kumagai, Hajime; Sawatari, Hiroyuki; Hoshino, Tetsuro; Konishi, Noriyuki; Murase, Yoko; Urabe, Ayako; Nomura, Atsuhiko; Sasanabe, Ryujiro; Shiomi, Toshiaki
Summary: Obstructive sleep apnea leads to excessive daytime sleepiness and cognitive dysfunction, which are risk factors for motor vehicle collisions. We aimed to clarify if vehicles with an advanced emergency braking system could reduce motor vehicle collisions caused by falling asleep while driving among patients with untreated obstructive sleep apnea. We enrolled patients with untreated obstructive sleep apnea who underwent polysomnography. The questionnaires included the Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index, history of drowsy driving accidents, and use of an advanced emergency braking system. Multivariate analysis was performed, and odds ratios and 95% confidence intervals were calculated. This study included 1097 patients (mean age, 51.2 ± 12.9 years). Collisions caused by falling asleep while driving were recorded in 59 (5.4%) patients, and were more frequently observed in vehicles without an advanced emergency braking system ( p = 0.045). Multivariate analysis showed that these collisions were associated with use of an advanced emergency braking system (odds ratio [95% confidence interval]: 0.39 [0.16–0.97], p = 0.04), length of driving (2.79 [1.19–6.50], p = 0.02), total sleep time (2.40 [1.62–3.55], p < 0.0001), sleep efficiency (0.94 [0.90–0.98], p = 0.003) and periodic limb movement index (1.02 [1.01–1.03], p = 0.004). The collision risk caused by falling asleep while driving in vehicles with an advanced emergency braking system was significantly lower. This study indicates that advanced emergency braking systems may be a preventive measure to reduce motor vehicle collisions among patients with untreated obstructive sleep apnea.